ENGLISH TEACHING METHODS USED BY TEACHERS OF ELEMENTARY SCHOOL - Desi Nuraeni Abudin, - (2010)
The present study, entitled English Teaching Methods used by Teachers of Elementary School (A Qualitative Research towards Fourth-Grade English Teachers in one of elementary school in central Bandung, West Java) portrays the methods implemented by English teachers in one of the elementary schools in central Bandung, West Java. This study is qualitative in nature, involving two English teachers of Elementary schools in Central Bandung. The data for the study were collected through observation, interview, and document analysis. The data collected were analyzed on the basis of the central theme posted in research question (1) What methods are used by the teacher in teaching English to young learners? (2) What benefits and challenges are faced by the teacher in using those methods? The findings of this study show that the two teachers used the Grammar Translation Method (GTM) in teaching process. T1 combined the Grammar Translation Method (GTM) with the Communicative Language Teaching (CLT) while T2 combined the Grammar Translation Method (GTM) with the Total Physical Response (TPR). However, they sometimes find difficulties in applying those methods on developing activities in the classroom that can motivate the students. Therefore, teachers' trainings on developing activities in the classroom should be conducted